“Las metodologías activas orientadas a la investigación para el aprendizaje en los docentes de la Unidad Educativa 19 de Septiembre del Cantón Salcedo” - Granja Cueva, Sonia Mercedes (2020)
The current educational systems face great problems, these problems are common in all the institutions of the country, in the XXI century the omniscient teachers are still in force, that is to say, it is believed that they know everything, prepared to give orders and kill the creativity and autonomy of students. In this context, the results of classroom visits carried out by institutional managers reveal great shortcomings of teachers in the teaching-learning process. One of the factors of great impact is the use of traditional teaching strategies that do not contribute to the development of learning, the teacher is still the only active actor in the class, the master classes, the vertical relationship in the classroom and the transmission continue knowledge mechanics. In this framework, it is necessary to tackle the problem urgently in such a way that this pedagogical gap of teacher-centered teaching is overcome and we move towards teaching that prioritizes learning and research. The main objective of this work is to develop active methodologies through workshops that promote research for learning aimed at teachers of the Educational Unit September 19. The present investigation is based on the quantitative paradigm, due to its level of depth and objectives it is a descriptive and explanatory investigation, the applied techniques were the survey and the structured interview, questionnaires were used to collect information. The results are the lack of knowledge of active learning methodologies and research for learning. The proposal aims to contribute to the training of teachers in active strategies that promote research as a resource for learning. From this perspective, the product of this research has been elaborated with a constructivist approach, it has as fundamental premises the construction of significant learning, collaborative work and motivation for the activation of knowledge.